Effect of garlic oil and vitamin E on productive performance and some hematological and biochemical blood parameters of Awassi male and female lambs - Amar Raeed Mohammed Thamer; Wissam Jasim Mohammed Ali; Wassem Khalid Ahmad (Kufa Journal for Agricultural Sciences)
This study was performed to evaluate the efficacy of garlic oil and vitamin E on Awassi lambs performance and some blood biochemical contents. The experiment conducted in farm of Baibokht (8 km north of Mosul city) from 12/2/2019 to 13/4/2019. Fifteen Awassi lambs at age one month and average weight 9.5±0.69 kg were randomly divided into three groups, (five lambs per group). The treatments were as follow, First group as control, the second group was given capsules 2 ml garlic oil. lamb-1.day-1 and the third group was given capsules 2 ml garlic oil + 400 international unit (IU) of vitamin E lamb-1.day-1, respectively. Lambs were staying with their mothers for suckling milk. The results showed a significant decrease for the second and third groups compared with control in cholesterol and triglycerides concentrations. The third group showed a significant increase in total and daily weights gain compared to second and control group. No significant effects were detected among treatments for white blood cells (WBC) and red blood cells (RBC) number, and the concentrations of hemoglobin, total protein, albumin and globulin, and the range of packed cell volume (PCV). In general, the addition to the diet garlic oil and vitamin E could led to improved body weight and some blood parameters of Awassi lambs.